Enhancing engine oil performance with graphene-cellulose nanoparticles: insights into thermophysical properties and tribological behavior - Alotaibi, Jasem Ghanem; Alajmi, Ayedh Eid; Kadirgama, Kumaran; Samylingam, Lingenthiran; Aslfattahi, Navid; Kok, Chee Kuang; Ramasamy, Devarajan; Wan Sharuzi, Wan Harun; Veerendra, A. S.; Sivaraos, Subramaniam; Yousif, Belal F (Frontiers Media S.A., 2025)
This study explores the development and optimization of a novel nano lubricant by incorporating graphene-cellulose nanoparticles into SAE 10W-40 engine oil to enhance its thermophysical and tribological performance. The nano lubricants were prepared with varying concentrations (0.01%, 0.03%, and 0.05% by volume) and subjected to a comprehensive evaluation of their thermal conductivity, dynamic viscosity, and tribological properties under operational conditions. The thermal conductivity analysis demonstrated that the inclusion of graphene-cellulose nanoparticles improved heat transfer capabilities, particularly at higher concentrations, while maintaining stability over a wide temperature range (30°C–90°C). The dynamic viscosity measurements revealed a synergistic effect of graphene and cellulose, enhancing dispersion stability and lubrication characteristics, with optimal performance achieved at 0.03% concentration. Tribological testing confirmed a significant reduction in the coefficient of friction, achieving a value as low as 0.0406, demonstrating improved wear resistance. Response Surface Methodology was employed to optimize the input parameters, providing insights into the interactions between concentration, load, speed, and temperature. The findings highlight the potential of graphene-cellulose nanocomposites as sustainable, high-performance additives for automotive lubricants, paving the way for energy-efficient and durable applications in the automotive and industrial sectors.